Status of Cacao (Theobroma cacao L.) production on its challenges and prospect in Zamboanga del Norte Province in the Philippines - Magallon, W. N.; Patalinghug, M. E.; Tangalin, MG. G. (International Journal of Agricultural Technology, 2022)
Examining the status of cacao production, challenges, and prospects of cacao farmers in Zamboanga del Sur province were done in this study. The investigation revealed that cacao farming was practiced by males (244 or 65.10%) and female cacao farmers (34%) who are primarily married with secondary educational backgrounds. Most cacao farmers were their productive age ranging from 50-59 years old (42.93%), 40-49 years old (34.4%). However, fewer young people engaged in cacao farming aged below 40 years old (7.46%). Intercropping was observed (99.20%) with coconut (79.20%) and banana (14.67%) planted along with cacao. Pest infestation of stem borer (59.73%) and bugs (22.67%) were observed at a low level (79.20%) and controlled using Lamdacyhalothrin (86.40%) as a chemical spray. Moreover, cacao diseases in farms were at a low incidence level (74.13%), with vascular streak dieback (53.06%) as the most common disease among farms, and the method of controlling the spread was using chemicals (53.60%) and synthetic pesticides (100%) as a spray. Farms established 2 years from sowing (90.13%) observed farm management practices such as weeding twice a year (45.33%), fertilizer application 4 times a year (88.00%) using 1-3 bags per hectare (85.06%). Cacao trees produced 0.50-1.50 (50.00%) of seeds per tree. Cacao products are sold in dried form (60.98%) with prices ranging from 81-100/kilogram through cooperative (100%). Farmers faced numerous challenges, the most significant of which were the high cost of routine maintenance (such as cleaning/brushing) and shortage of laborers. The accessibility from the farm to the market road was also seen as a challenge among them. The province’s cacao agricultural stakeholders extended to support services to farmers such as free planting materials, credit assistance, cacao production seminars, and post-harvest facilities, which were all considered valuable to farmers in addressing the challenges they faced on cacao farming and production